Emerging Role of Serum Glucocorticoid-Regulated Kinase 1 in Pathological Pain - Liu, Baowen; Li, Ningbo; He, Zhigang; Zhang, Xianwei; Duan, Guangyou (Frontiers in Molecular Neuroscience, 2021)
Currently, the management of acute and chronic pain in clinical practice remains unsatisfactory due to the existence of limited effective treatments, and novel therapeutic strategies for pathological pain are urgently needed. In the past few decades, the role of serum and glucocorticoid-inducible kinase 1 (SGK1) in the development of pain and diurnal rhythms has been implicated in numerous studies. The expression levels of SGK1 mRNA and protein were found to be elevated in the spinal cord and brain in various pathological pain models. Blocking SGK1 significantly attenuated pain-like responses and the development of pathological pain. These studies provide strong evidence that SGK1 plays a role in the development of various types of pathological pain and that targeting SGK1 may be a novel therapeutic strategy for pain management. In this review, we provide evidence from animal models for the potential role of SGK1 in the regulation of pathological pain caused by inflammation, nerve injury, psychiatric disorders, and chronic opioid exposure.